CONSUMER PERCEPTION OF GLOBAL VS LOCAL BRANDS BETWEEN WALLS AND CAMPINA ICE CREAM IN MANADO - Kiwol, Diana Natalia; Mekel, Peggy Adeline (Universitas Sam Ratulangi, 2014)
Food brand is one main concern for a lot of people in every city or region in each part of this world when purchasing and using products or choosing and spending services, without denying the importance of features and quality of available items. This aim of study perception of global and local brand in Manado between Walls and Campina ice cream with five important element: sensation, absolute threshold, differential threshold, subliminal threshold and consumer perception. The method that used in this research is Independent Sample t-test. Independent Sample t-test is a method to compares the mean score of two groups on given variable. The fact that Walls ice cream has become more popular for the majority in Manado, compared with comparable products from Campina. The companies management from Walls and Campina ice cream Â product in the Manado City must be aware with common customersâ€™ concern about sensation factor (include products, packages, brand names,advertisements and commercials) because it can directly impact to cunsumers. Keywords: consumer perception, local brand